2022
DOI: 10.3390/diagnostics12010193
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Role of Uric Acid to Creatinine Ratio for the Identification of Patients with Adverse Pulmonary Embolism Outcomes

Abstract: Background: Uric acid (UA) is the final product of purine metabolism and a marker of oxidative stress that may be involved in the pathophysiology of cardiovascular and thromboembolic disease. The aim of the current study is to investigate the potential value of UA to creatinine ratio (UA/Cr) as a diagnostic tool for the outcome of patients admitted with acute pulmonary embolism (PE) and the correlations with other parameters. Methods: We evaluated 116 patients who were admitted for PE in a respiratory medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It also doesn’t agree with another study, which showed that the uric acid/creatinine ratio (UA/Cr) was higher and statistically significant in pre-eclamptic women [ 23 ]. Previous studies have shown the association of UA/Cr with the severity of pulmonary embolism, the presence of COPD, lung function, hypertension, metabolic syndrome, type 2 diabetes, and malignancy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also doesn’t agree with another study, which showed that the uric acid/creatinine ratio (UA/Cr) was higher and statistically significant in pre-eclamptic women [ 23 ]. Previous studies have shown the association of UA/Cr with the severity of pulmonary embolism, the presence of COPD, lung function, hypertension, metabolic syndrome, type 2 diabetes, and malignancy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…No previous studies have been conducted to predict the relationship between serum UA/Cr (UA/Cr was calculated by dividing serum uric acid by serum creatinine) and the severity of PE. Previous studies have shown an association between UA/Cr and PE severity, the presence of chronic obstructive pulmonary disease (COPD), lung function, hypertension, metabolic syndrome, type 2 diabetes, and malignancy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma level of UA can be used as a risk marker for thrombosis and prognostic stratification among PE patients [ 36 , 37 ]. Therapies targeted at lowering UA are associated with reduced risk of major adverse cardiovascular events [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%